5-fluorouracil-loaded chitosan microspheres: Preparation and release characteristics - (:unkn) unknown (TAYLOR & FRANCIS LTD, 1996)
Cross-linked chitosan microspheres containing 5-Fluorouracil (5-FU) were prepared. Variables believed to be important for microsphere properties were examined; these included: drug and chitosan concentrations, cross-linking process, the type of oil, stirring rate and also additives. Initial 5-FU concentration, the type and concentration of chitosan, the viscosity of oil phase and glutaraldehyde concentration affected drug release from chitosan microspheres. 5-FU release from cross-linked chitosan microspheres is characterized by an initial rapid release of drug. Addition of substances such as alginic acid, chitin, agar, sodium caprylate and stearic acid changed the release properties of 5-FU microspheres.
Keywords: 5-fluorouracil; chitosan; microsphere; drug release